Effect of seat tube angle on the work efficiency of lower limb muscles during cycling - Chung, K. R.; Hyeong, J. H.; Kim, S. Y.; Choi, C. H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The effect of seat tube angle (STA) on work efficiency at lower limb muscle was evaluated during a pedal rotation using inverse dynamic model. Since the target is not professional cyclist, the various seat tube angles of 78, 68, 58 and 48 degrees was investigated. Cycling simulation was performed at 250W and 60rpm. The works of individual muscle of lower limb and the total work was estimated. The result shows that the total work of single leg at seat tube angles of 78, 68, 58 and 48 degrees were 168.1(J), 167.9(J), 168.9(J) and 170.8(J) respectively. In conclusion, the exertion of lower limb for delivering same amount of work to the crank is the smallest at around 72 degree of seat tube angle which mean work efficiency of lower limb is the greatest